2020
DOI: 10.1021/acsanm.0c02333
|View full text |Cite
|
Sign up to set email alerts
|

MnOx–CeOx Nanoparticles Supported on Porous Hexagonal Boron Nitride Nanoflakes for Selective Catalytic Reduction of Nitrogen Oxides

Abstract: In selective catalytic reduction (SCR) technology, aggregation of the catalyst generally degrades the performance for converting nitrogen oxides into harmless gases. To avoid such performance degradation and to achieve a noticeable improvement in the SCR performance, good dispersion of the catalyst on the support is required. In this study, we synthesized MnO x −CeO x catalytic nanoparticles on surface-modified supports and studied the dispersion behavior of the catalyst on the support. Hexagonal boron nitride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In addition to photocatalysis, which is the most studied application by far, h‐BN nanocomposites as electrocatalysts have also been designed. [ 91–95 ] Patil et al have reported a method to prepare an h‐BN‐manganese oxide (MnO x ) composite by adding h‐BN during the reducing process of potassium permanganate (KMnO 4 ). [ 91 ] h‐BN supports the growth of MnO x nanorods due to the seeding role played by the h‐BN surface.…”
Section: Boron Nitride–metal Compound Heterostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to photocatalysis, which is the most studied application by far, h‐BN nanocomposites as electrocatalysts have also been designed. [ 91–95 ] Patil et al have reported a method to prepare an h‐BN‐manganese oxide (MnO x ) composite by adding h‐BN during the reducing process of potassium permanganate (KMnO 4 ). [ 91 ] h‐BN supports the growth of MnO x nanorods due to the seeding role played by the h‐BN surface.…”
Section: Boron Nitride–metal Compound Heterostructuresmentioning
confidence: 99%
“…Another example is the h‐BN/MnCe hetero‐catalyst for selective catalytic reduction (SCR) technology. [ 92 ] Aggregation of the catalyst, which reduces the conversion of nitrogen oxides into nontoxic gases, is the main drawback in SCR. A dispersion of the catalyst on proper support is a possible solution, and h‐BN has been tested as a potential candidate.…”
Section: Boron Nitride–metal Compound Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study was conducted using hexagonal boron nitride, which has a high melting point of 3000 °C and excellent thermal stability, as a support synthesized h-BN with a porous structure on the surface due to catalytic etching by the transition metal. When the active material is dispersed in this porous structure, the phase is thermally stabilized with high dispersibility, and phase changes and agglomeration are suppressed [ 97 ]. As a result, it was possible to nano-disperse the catalytically active material down to 10 nm by utilizing the surface defect anchoring sites.…”
Section: Dispersion Of Active Catalytic Materialsmentioning
confidence: 99%
“…Notably, h-BN can be synthesized in the shape of a plate owing to its structural properties, and it promotes the dispersion of catalytic species [ 34 ]. In addition, it is considered as a potential material in many research fields owing to its excellent properties, such as high thermal stability and conductivity originating from stable bonding and outstanding chemical stability [ 35 ]. These advantages render it suitable for long-term operation under high temperatures during NH 3 -SCR, which also involves toxic atmospheres.…”
Section: Introductionmentioning
confidence: 99%